Islamophobia in European cities: Solidarities, responses, and dilemmas for young balkan muslims - Trupia, Francesco (London Routledge, 2025)
The demise of socialism in Southeast Europe coincided with the breakout of wars and genocidal violence against local Muslim populations. After being displaced and forced to migrate to different European countries, those former socialist citizens quickly developed institutions of sociability and unobtrusively enacted postulates of solidarity. This book brings a spotlight on the (3z(Bgenerations after(3y (Bborn to Balkan Muslim families whose repatriation could not take place due to the continuous political instability and insecurity in their homelands.s